2023
DOI: 10.1038/s41467-023-36332-3
|View full text |Cite
|
Sign up to set email alerts
|

Myristic acid as a checkpoint to regulate STING-dependent autophagy and interferon responses by promoting N-myristoylation

Abstract: Stimulator of interferon gene (STING)-triggered autophagy is crucial for the host to eliminate invading pathogens and serves as a self-limiting mechanism of STING-induced interferon (IFN) responses. Thus, the mechanisms that ensure the beneficial effects of STING activation are of particular importance. Herein, we show that myristic acid, a type of long-chain saturated fatty acid (SFA), specifically attenuates cGAS-STING-induced IFN responses in macrophages, while enhancing STING-dependent autophagy. Myristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 52 publications
0
3
1
Order By: Relevance
“…Recently, it was shown that ARF1 may also have a role in autophagy. However, our data show that cGAS-STING activation by the ARF1 R99C mutation is not mediated by autophagy 55 . Future studies are needed to genetically dissect the relative contribution of autophagy-mediated STING turnover and ARF1-mediated STING recycling to overall cGAS/STING signal termination.…”
Section: Discussioncontrasting
confidence: 63%
“…Recently, it was shown that ARF1 may also have a role in autophagy. However, our data show that cGAS-STING activation by the ARF1 R99C mutation is not mediated by autophagy 55 . Future studies are needed to genetically dissect the relative contribution of autophagy-mediated STING turnover and ARF1-mediated STING recycling to overall cGAS/STING signal termination.…”
Section: Discussioncontrasting
confidence: 63%
“…Myristic acid has previously been described to have antifungal [89,90] and antiinflammatory effects [91]. Additionally, myristic acid has been identified as a metabolic checkpoint that regulates autophagy and type I IFN responses [92]. In the present study, we confirmed that the IL-10 production of LPS-treated moDCs can be inhibited in the presence of myristic acid.…”
Section: Discussionsupporting
confidence: 82%
“…Myristic acid has recently emerged as a regulator of STING degradation via N-myristoylation of ARF1, which is involved in directing the membrane trafficking and autophagic degradation of STING, thereby limiting cGAS-STING-induced interferon response. Upon viral infection the production of myristic acid is reduced due to a disruption in the cellular lipid metabolism, which alleviates autophagy-dependent STING degradation ( 160 ).…”
Section: Interactions Of Autophagy With the Cgas-sting Pathwaymentioning
confidence: 99%